PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KIMIA PADA PESERTA DIDIK DALAM MATERI IKATAN KIMIA DI KELAS X MIPA 5 SMA NEGERI 2 MALANG - Rifngatun Hayati (Arfak Chem: Chemistry Education Journal, 2019)
Abstract This research is a Classroom Action Research that aims to improve learning outcomes of chemistry in class X MIPA 5 students with chemical bonding material at SMA Negeri 2 Malang in the 2019/2020 academic year using the application of the Discovery Learning learning model.  In this study using 3 cycles.  The results showed that there was an increase in student learning outcomes after the application of the discovery learning model, namely in cycle 1 of 65.5;  in the second cycle 72 and the third cycle of 8. Keywords: Classroom Action Research, Chemical Bond, Discovery Learning, Learning outcomes